Front Cover: Unveiling Organocatalysts Action – Investigating Immobilized Catalysts at Steady‐State Operation via Lab‐on‐a‐Chip Technology (ChemCatChem 24/2021). Issue 24 (25th November 2021) - Westphal, Hannes; Warias, Rico; Becker, Holger; Spanka, Matthias; Ragno, Daniele; Gläser, Roger; Schneider, Christoph; Massi, Alessandro; Belder, Detlev
Abstract : The Front Cover illustrates a vortex that engulfs entire laboratory equipment and turns it into a single chip unit on the other side. In their Full Paper, H. Westphal, R. Warias et al. present a method to study immobilized organocatalysts and their performance in stereoselective transformations. This is done by utilizing a single chip‐based device combining a packed bed microreactor running in a truly continuous fashion and a miniaturized chiral HPLC unit coupled to Electrospray Ionization Mass Spectrometry. Not only insights into the catalyst's steady states and overall long‐term activities can be investigated, but also it is possible to clarify their stereoselectivity right on‐stream. Thus, this method provides a sustainable and rapid method for catalyst discovery and optimization at smallest scales. More information can be found in the Full Paper by H. Westphal, R. Warias et al.